Life metabolism - Gao deng jiao yu chu ban she (Oxford University Press, 2022)
'Life metabolism' is a fully open access, peer-reviewed journal that aims to publish works of high significance and broad interest in all areas of metabolism.
Keywords: Metabolism : Periodicals; Metabolism; Metabolism